2001
DOI: 10.1002/1529-0131(200110)45:5<430::aid-art362>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Combined spa–exercise therapy is effective in patients with ankylosing spondylitis: a randomized controlled trial

Abstract: Objective. To determine the efficacy of combined spa-exercise therapy in addition to standard treatment with drugs and weekly group physical therapy in patients with ankylosing spondylitis (AS). Methods. A total of 120 Dutch outpatients with AS were randomly allocated into 3 groups of 40 patients each. Group 1 (mean age 48 ؎ 10 years; male:female ratio 25:15) was treated in a spa resort in Bad Hofgastein, Austria; group 2 (mean age 49 ؎ 9 years; male:female ratio 28:12) in a spa resort in Arcen, The Netherland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
0
20

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(143 citation statements)
references
References 10 publications
(16 reference statements)
4
119
0
20
Order By: Relevance
“…the calculations employed a random effects model. In trials comparing two similar exercise groups and one control group, the exercise group results were pooled for comparative purposes [12,13]. In the event that the published data from included studies were insufficient to calculate pooled effects, study authors were contacted requesting additional data.…”
Section: Data Collection and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…the calculations employed a random effects model. In trials comparing two similar exercise groups and one control group, the exercise group results were pooled for comparative purposes [12,13]. In the event that the published data from included studies were insufficient to calculate pooled effects, study authors were contacted requesting additional data.…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…1 [20]. Frequency of exercise varied from twice daily [19] to once weekly [21][22][23], with individual session duration ranging from 30 min [18,[24][25][26][27][28][29]] to 3 h [13]. traditional therapeutic exercises targeting flexibility, posture and respiration predominated.…”
Section: Study Selectionmentioning
confidence: 99%
“…Also, home exercise of this kind is time-efficient, economical and convenient [6][7][8][9][10]. Alternative exercise programs such as swimming, spa-exercise therapy and tai chi programs have also been studied in AS patients, and led to a significant reduction in disease activity and improvement in function compared to the control groups [30][31][32][33]. But the major challenge is the widely observed fact that most AS patients do not exercise on a regular basis.…”
Section: Discussionmentioning
confidence: 99%
“…Daily hydrotherapy and swimming can improve general fitness while protecting the joints. Although a Cochrane review concluded that there is little evidence for the effectiveness of non-pharmacological management, expert opinion and clinical experience suggest that individuals benefit from intensive physiotherapy [29].…”
Section: Managementmentioning
confidence: 99%